Strategies for the Development of 6–8-Year- Old Children’s Breathing for Singing - Davidova, Jelena; Zavadska, Galina; Rauduvaitė, Asta; Chuang, Ming Jen (Pedagogika, 2017)
On the basis of the diagnostic results yielded by the international project “The Coordination between Musical Hearing and Vocal Apparatus of 6–8-Year-Old Children during the Process of Singing: Comparative Study in Latvia, Lithuania and Taiwan”, strategies for the development of 6–8-year-old children’s breathing for singing were formulated in three areas (breath support, formation of the sensation of inhalation and exhalation, and breath energy), as well as exercises for the development of correct breathing in singing were devised. Research aim: to design strategies for developing 6–8-year-old children’s breathing for singing.